2018
DOI: 10.1002/phar.2065
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Infusion for Adjunct Sedation in Mechanically Ventilated Adults

Abstract: Continuous ketamine infusion for adjunct light sedation was well tolerated in a cohort of critically ill adults, with an acceptable safety profile. Prospective studies of ketamine infusion are warranted to further establish its efficacy as a sedative in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
67
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 18 publications
6
67
1
3
Order By: Relevance
“…These results coincide with a study that found adjunctive continuous infusion ketamine used for light sedation promoted concomitant sedative reduction while increasing the number of documented goal Riker Sedation‐Agitation Scale scores in 24 hours . Our results further add to these findings with a time‐dependent, dose‐quantitative analysis of analgosedative requirements, inclusion of comprehensive concomitant analgesic‐sedative infusions, and unique identification of population characteristics associated with positive ketamine response in the general ICU population.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These results coincide with a study that found adjunctive continuous infusion ketamine used for light sedation promoted concomitant sedative reduction while increasing the number of documented goal Riker Sedation‐Agitation Scale scores in 24 hours . Our results further add to these findings with a time‐dependent, dose‐quantitative analysis of analgosedative requirements, inclusion of comprehensive concomitant analgesic‐sedative infusions, and unique identification of population characteristics associated with positive ketamine response in the general ICU population.…”
Section: Discussionsupporting
confidence: 89%
“…Continuous infusion ketamine dosing observed in the current study falls within broad published data ranges of 0.125 to 2 mg/kg/hour for analgosedative effects . We chose to report ketamine dosing as μg/kg/minute per institutional practice – translated median doses used within the current study range from 0.3 to 0.4 mg/kg/hour.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations